Classification analysis of blue and green water quantities for a large-scale watershed of southwest China. (1st November 2022) - Li, Yutong; Cai, Yanpeng; Wang, Xuan; Li, Chunhui; Liu, Qiang; Sun, Lian; Fu, Qiang
Abstract: Traditional blue water resources assessment and management may not meet the needs of sustainable water resource utilization; ignoring the number of green water resources will underestimate the availability of water resources. To rationally allocate and scientifically manage the limited water resources, it is necessary to divide the rich and poor flow situation of blue water and green water. The MIKE SHE-MIKE HYDRO integrated coupled model was selected and used in the Yalong River basin to ascertain the blue and green water in the hydrological cycle. The model was calibrated by matching simulated discharge against observed streamflow discharge at the Tongziling Station. At the same time, the research analyzed the component of green water and the total amount of blue water or green water on a temporal scale. The set pair analysis (SPA) was introduced to classify blue water and green water, which can not only understand the amount and distribution characteristics of water resources in the Yalong River Basin but also rationally allocate the total of water resources in the basin from the perspective of the regional water cycle. Furthermore, according to the situation of blue water and green water in the basin, the related policies are formulated to realize the efficient utilization of water resources in the Yalong River basin. Highlights: A high-resolution hydrological model of the Yalong river basin is bulit. The MIKE SHE system as the modeling platform is used to obtain the variation of Bluewater and Greenwater. The set pair analysis (SPA) was introduced to study the variation of rich and poor Bluewater and Greenwater. Table Captions.